Advances in the pathogenesis of rosacea - Wang, Hui; Zhou, Cheng (Frontiers in Immunology, 2026)
Rosacea is a chronic inflammatory cutaneous disorder predominantly affecting the centrofacial region, whose pathogenesis is complex and not yet fully understood. In this review we summarized the latest significant advances in the pathogenesis of rosacea in recent years. In genomic studies, the application of bioinformatics techniques such as whole-genome sequencing has identified novel susceptibility genes and linked multiple pathogenic mechanisms. Neurovascular dysfunction resulting from abnormal neuropeptides expression and dysregulated amino acid metabolism constitutes an important pathogenic factor in rosacea. The TLR2/LL-37/mTORC1 signaling axis, as a core regulatory pathway in innate immunity has been elucidated in detail. In addition, the dysbiosis of skin and gut microbiota, together with the impairment of skin barrier function, is also closely associated with the onset and progression of this disease. The deeper understanding of the pathogenesis of rosacea will benefit the development of new drugs and promote individualized diagnosis and treatment.